Investigating Drip Infusion Speed Control: A Study of Weight and Pinch Methods Concerning Subject Variations - Agustine, Lanny; Astarini, Made Indra Ayu; Manungkalit, Maria; Pranjoto, Hartono (Social Science and Humanities Journal, 2025)
An infusion drip system that utilizes a clamp method to control the drip rate has not yet achieved a consistent drip rate across different subjects. The condition was that each movement of the pinch valve did not consistently stimulate the release of one drop of liquid. In this study, tests were conducted with variations in the pinch-release period (3 seconds, 2.5 seconds, 2 seconds, and 1.5 seconds) and variations in the release pinch valve duration (55 milliseconds, 60 milliseconds, 65 milliseconds, 70 milliseconds, and 75 milliseconds). The testing involved 15 participants, including 100 cc of NaCl infusion fluid for 1-2 hours. The results indicated two variations in drip speed among all test subjects: it required either two ticks to produce one drop of infusion (the dominant outcome) or just one tick. Based on tests with healthy participants and their responses to questionnaires, it was concluded that the device was quite comfortable to use with the release pinch valve duration of 60-70 milliseconds and a pinch-release period of 2 seconds, 2.5 seconds, or 3 seconds.